Sea slugs (Gastropoda: Heterobranchia) from two remote reefs of the Southern Gulf of Mexico: Cayo Arenas and Cayo Arcas - Deneb Ortigosa; Nuno Simões (Revista Mexicana de Biodiversidad)
Two field trips were made during 2017 to Cayo Arenas and Cayo Arcas, southern Gulf of Mexico. Direct and indirect sampling methods focused on shell-less marine heterobranchs were carried out. As a result, 30 species of sea slugs are reported for the first time from these 2 remote reefs off the Yucatán Peninsula. From these, 7 species hold new distribution records for the Gulf of Mexico: Sclerodoris worki, Platydoris angustipes, Polycera odhneri, Hexabranchus morsomus, Limenandra nodosa, Petalifera ramose, and Hermaea cruciata. Hexabranchus morsomus is a considerable west geographical range extension from the known distribution range, so far restricted to the Caribbean Sea. Nine specimens were identified up to genus level: Cuthona sp., Haminoea sp., Petalifera sp. and Elysia sp. With the present contribution, the sea slug richness in the Campeche Bank increases to 94 species.